Effects of Principles of Corporate Governance on Management of Early Childhood Education in Bahati Division Nakuru County - Kithuku, Roselyne M; Odundo, Paul A (OSR Journal of Research & Method in Education, 2016)
This study sought to examine the effects of principles of corporate governance onmanagement of early childhood education (ECE) in Bahati Division Nakuru County, Kenya. These were necessitated by the desire to establish whether schools are applying principles of corporate governance in managing school affairs. Proper application of corporate principals enables achievement of stated goals in management of ECE. The study draws a correlation between adoption of principals of corporate governance and performance of the ECE sector. Thus the study seeks to determine the effects of principles of corporate governance on management of ECE in Bahati Division, Nakuru County, Kenya. These were guided by the following objective; To determine adherence to the principle of full disclosure and Transparency in ECE management in Bahati Division, Nakuru North Sub-County. The research adopted a descriptive survey design. This was suitable in this study as it helped the researcher establish the existing levels of compliance with principals of corporate governance at theECE schools and their influence on performance. Adherence to full disclosure and transparency as the study found out requires publicly revealing shareholder and ownership rights and company objectives. This plays a major role in the effective and productive Early Childhood Education management and sustainability of these institutions. As the study found out from the respondents in Bahati division Nakuru north sub-county, majority of respondents indicated that internal control systems, access to information and budgetary control were major assessment points in transparency in ECE management. Other determinants of transparency in ECE management as the study found out from the respondents were periodic reporting whereby management reports on the issues happening within or outside institutions that may have an impact on the shareholders and every stakeholder, another was control and feedback mechanisms whereby stakeholders were free to communicate and convey information expect feedback from management. Disclosure of material matters concerning the institution should be timely and balanced to ensure that all stakeholders and non-stakeholders have access, factual information. All this the study found that may play a major role in the success or failure of effective ECE management with regard to corporate governance.
Keywords: Early Childhood Education; Corporate Governance